Rapid, Sensitive and High-Throughput Screening Method for Detection of SARS-Cov-2 Antibodies by Bio-Layer Interferometry - SR, Lokireddy; SR, Kunchala; RP, Godavarthy; VSK, Kona; L, Avula; RK, Mishra; MR, Nalam (Archives of Clinical and Medical Case Reports, 2021)
In the present pandemic scenario, there exists an unmet global need for the development of a rapid and sensitive method for the detection and sero-surveillance of SARSCoV- 2 infection. The currently available options for identification of SARS-CoV-2 infection include detection of viral RNA by RT-PCR, antigen testing by Lateral Flow Assay (LFA) or antibody detection by Enzyme Linked Immunosorbent Assay (ELISA), LFA, chemiluminescence immunosorbent assay and immunofluorescence assay. Though many kits are available commercially to detect antibodies against SARS-CoV-2, none of them are simple, sensitive and high throughput. To overcome these limitations, we have developed a diagnostic method, the Bio- Layer Interferometry Total Antibody Assay (BLI-TAA) that uses the principle of BLI-TAA using "dip-and-read" format to detect antibodies (IgM/IgA/IgG) against SARS-CoV-2 virus during and after the infection. The BLI-TAA method provides real-time optical measurements of antigen loading, plasma antibody binding. This BLI-TAA based approach uses two recombinant proteins that include SARS-CoV-2 Spike S1 subunit and Nucleocapsid proteins to capture anti- SARS-CoV-2 antibodies (IgM/IgA/IgG) in serum or plasma or blood during and after SARS-CoV-2 infection. BLI-TAA shows very high sensitivity and specificity for detection of antibodies against SARS-CoV-2 virus compared to the existing standard ELISA. In addition to detecting of antibodies against SARS-CoV-2 virus, it can also be used for rapid screening of antibodies for vaccine development, clinical management of the disease, in the screening of antiviral therapy, evaluation of the convalescent plasma for COVID-19 antibody titers and sero-surveillance in epidemiological studies.